Inside the politics of technology : agency and normativity in the co-production of technology and society - Harbers, Hans (Amsterdam University Press, 2005)
"Man is the measure of all things, an old saying goes. But it is a bad guide for understanding scientific and technological culture. Science and technology are not simply the means to reach human ends; they also actively shape human beings, their goals, meanings and social relations. This volume discusses the implications of this so-called 'co-production' of science, technology and society for our analytical as well as normative ideas about humanity, technology and the relations between both. Addressing issues such as cancer genetics, prenatal screening and ecological consequences of traffic and transport, contributors argue that technology has its own kind of sub-politics, which in turn calls for policies of technology: from steering and regulation to scenario studies, in order to achieve democratisation of technology"--Publisher's description